Big Data and the Opioid Crisis: Balancing Patient Privacy with Public Health. Issue 2 (2018) - Butler, John Matthew; Becker, William C.; Humphreys, Keith
Abstract : Parts I through III of this paper will examine several, increasingly comprehensive forms of aggregation, ranging from insurance reimbursement "lock-in" programs to PDMPs to completely unified electronic medical records (EMRs). Each part will advocate for the adoption of these aggregation systems and provide suggestions for effective implementation in the fight against opioid misuse. All PDMPs are not made equal, however, and Part II will, therefore, focus on several elements — mandating prescriber usage, streamlining the user interface, ensuring timely data uploads, creating a national data repository, mitigating privacy concerns, and training doctors on how to respond to perceived doctor-shopping — that can make these systems more effective. In each part, we will also discuss the privacy concerns of aggregating data, ranging from minimal to significant, and highlight the unique role of stigma in motivating these concerns. In Part IV, we will conclude by suggesting remedial steps to offset this loss of privacy and to combat the stigma around SUDs and mental health disorders in general.